Insights of Trauma from Arundhati Roy’s, “The Ministry of Utmost Happiness - S. Leena Devanesam; V.Manimozhi (International Journal of Psychosocial Rehabilitation, 2020)
No man in the world is without grief. Every person has got their own burden to carry in their life. But few only experience trauma during their lifetime. It stands for a deeply distressing experience in a person. This journal enumerates the medically traumatic experience of Arundhati Roy’s few characters like Amrik Singh, Loveleen Singh Nee Kaur who had suffered destructive and traumatic events such as torture, indefinite periods of incarceration and separation from family. This paper also deals with medical traumatic experiences of Maryam Ipe the mother of Tilo. She was isolated from family due to her secret unworthy relationship with low strata man. The solitary feelings worked inwardly in her thoughts, words, and mind throughout her entire life despite her career achievements. In her last stages, she became medically traumatized.